Comparative Long-Term Performance of Short Implants and Sinus Lift Approaches in Posterior Maxillary Rehabilitation - Jumanazarovich, Saparbayev Zakir (Journal of Science in Medicine and Life, 2025)
Background: Traditionally, vertical maxillary atrophy has been managed using sinus lift procedures combined with implant placement, performed either simultaneously or in two surgical stages. The introduction of the transcrestal sinus lift expanded clinical indications while reducing morbidity. More recently, short implants have gained recognition as a reliable alternative, even in cases of significant horizontal bone loss, as they often permit direct implant placement without extensive augmentation. This study aimed to compare the clinical outcomes of short implants placed in severely atrophic maxillary ridges with those of conventional-length implants placed following lateral sinus elevation. Methods: A retrospective split-mouth study was carried out to evaluate conventional lateral sinus elevation with standard-length implants versus the use of short implants for posterior maxillary vertical bone deficiency. The primary outcome measure was marginal bone level change. Secondary outcomes included implant survival and complication rates. Categorical variables were assessed using the Chi-squared test or Fisher’s exact test, while continuous variables were compared using the Wilcoxon test. Statistical significance was defined as p < 0.05. Results: The study included 24 patients and 73 implants in total. The lateral sinus elevation group (LSEG) comprised 39 implants, while the short implant group (SIG) comprised 32. All restorations were screw-retained. Both groups showed marginal bone loss of less than 0.5 mm, with no statistically significant differences between them. Within the LSEG, two cases of mucositis were documented, both associated with improper interdental brush use, along with two prosthetic screw fractures as technical complications. Conclusions: Long-term findings indicate that short implants demonstrate clinical outcomes comparable to those achieved with conventional sinus augmentation and implant placement, particularly regarding implant survival, marginal bone stability, and complication rates. These results support short implants as a valid and less invasive alternative for rehabilitating vertically atrophic posterior maxillae.